Establishment of Dissolution Kinetics and Mechanism of Direct Leaching of Gagi Phosphate Rock in Hydrochloric Acid Solution - Ayinla, K.I.; Baba, A.A.; Oyinloye, J.S.; Olaoluwa, D.T.; Ibrahim, A.S.; Raji, M.A.; Abdulrahman, A.; Ajetomobi, O.O. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2018)
Hydrochloric acid leaching kinetics of Gagi phosphate rock assaying 36.1% P2O5, 4.3% Al2O5, and 3.9% SiO2 was examined. The phosphate rock mineralogical characterization indicated that the major phase of the rock was Quartz (SiO2) with calcium aluminum phosphate as the major phosphate ore. The effect of different optimization parameters such as lixiviant concentration, system temperature, ore particle size and stirring speed were investigated. At selective extracted duration of 2 h with standard leaching condition of -70 + 63µm, 80°C, 0.20 M HCl and 300 rpm stirring speed, more than 84% P2O5 could be achieved. The leaching process kinetic mechanism was found to be surface diffusion controlling mechanism. The calculated reaction order and activation energy was 0.789 and 42.31 kJ/mol respectively. In addition, a mathematical expression including the experimental parameter to represent the kinetic of this leaching process was proposed in the study.